Fire Precautions at Antarctic Stations - Stonehouse, Bernard (Polar Record, 1953)
In 1946 the Falkland Islands Dependencies Survey station on Deception Island in the South Shetland Islands was completely destroyed by fire. Stores, valuable equipment and the records of many months' work were lost. In 1948 the station at Hope Bay in Trinity Peninsula was burnt down, with the loss of two lives. In January 1952 the hut of the French Antarctic Expedition at Port-Martin in Terre Adélie was destroyed in the same way. Smaller outbreaks of fire, fortunately detected early and dealt with promptly, have been reported from other stations. Of all the difficulties which can overtake a polar expedition, the loss of its base is perhaps the most disastrous. Nevertheless, the frequency with which such losses seem to occur suggests that there are fundamental errors in the design of the huts, as well as a tendency to underestimate the danger of fire.